Models, systems, networks in economics, engineering, nature and society - E.M. Bizhanova; V.M. Myskin; L.N. Semerkova (Модели, системы, сети в экономике, технике, природе и обществе)
Background. The need to quickly replace foreign software imports has led to significant growth in the relatively new information technology and industrial automation market. Despite the fact that companies have been automating their activities for more than 20 years, many of them have used foreign software until recently, which in modern conditions entails possible serious threats to their activities. This is what caused the growth of the domestic industrial automation market, and the rapid growth of new technologies, especially in the field of automation, gives reason to call this market innovative. At the same time, as in most markets, the established interaction chains have collapsed and business processes have become more complex. This prompted companies operating in it to offer their own business automation solutions and rebuild these chains: find new business partners, develop new interaction mechanisms. To improve the efficiency of companies in the innovative industrial automation market, it is necessary to describe the system of interaction of industrial automation market participants, understand the place of a specific company in this system, and build its activities in accordance with the mechanisms and trends operating in the market. Materials and methods. For a deeper understanding of the nature of interaction of innovative industrial automation market participants, the study will use a systems approach that will help not only to describe the behavior of the participants in the system, but also to describe the relationships existing between them and explain the interrelations between them. In addition, a systems approach will allow classifying market participants based on a specific unit of analysis and considering interactions from these positions. Results. The main elements of the system of interaction of innovative industrial automation market participants are considered. The peculiarity of the product in the market is revealed. The types of developer companies in the market and the conditions in which they are forced to work are considered, including barriers and restrictions imposed by market customers. The features of interaction of industrial automation market participants are revealed. Conclusions. It is concluded that knowledge of the specifics of interaction between innovative industrial automation market participants will increase the efficiency of the developer company and will also help to form its distinctive market advantages that will allow the company to stand out from its competitors.